Role of virgin coconut oil VCO as co-extractant for obtaining xanthones from mangosteen Garcinia mangostana pericarp with supercritical carbon dioxide extraction - Siew, Lee Kok; Wan, Jun Lee; Smith, Richard Lee; Suleiman, Norhidayah; Na Jom, Kriskamol; Vangnai, Kanithaporn; Sharaai, Amir Hamzah; Gun, Hean Chong (Elsevier BV, 2021)
Virgin coconut oil (VCO) was used as co-extractant with supercritical carbon dioxide (scCO2) extraction for obtaining xanthones from mangosteen pericarp (MP) without organic co-solvents. In each experiment, 120 g of dried MP that had median particle sizes of 0.85 mm was used. Extraction of MP with 40% VCO co-extractant using scCO2 (1.08 kg/h) for 420 min at 430 bar and 70 °C gave α-mangostin (32.2 mg/g), γ-mangostin (7.2 mg/g), xanthones (28.2 mg/g) in extract and an extraction yield of 31%. The role of VCO is that it promotes dissolution of xanthones and mass transfer into the scCO2 phase as elucidated with the Pardo-Castaño model. The Lentz equation was generalized in terms of (P, T, %VCO, ρCO2) to correlate all extraction curve data to within 7.4% and to estimate extraction yield crossover regions. Xanthones can be separated from mangosteen pericarp with VCO and scCO2 extraction without organic co-solvents.